2019
DOI: 10.12809/hkjr1916879
|View full text |Cite
|
Sign up to set email alerts
|

Characteristic Features of Breast Cancer in Women Aged ≤30 Years

Abstract: Objective:To identify and describe the imaging, clinicopathological and biological characteristics of breast cancer for women aged ≤30 years and to correlate the imaging features with clinical and molecular prognostic factors of breast cancer. Methods: A total of 47 women aged ≤30 years with diagnosed breast cancer were included in this study. The patients' clinic visit, radiology, and pathology reports were retrospectively reviewed. We analysed the associations between features and outcomes using Fisher's exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 29 publications
2
1
0
Order By: Relevance
“…A higher percentage of irregular margin is also observed in another study [22]. This finding is also supported by the study at Dong-A University Hospital and the University of North Carolina at Chapel Hill, USA [22]. Age has no impact margin, a finding similar to a study conducted in Japan [21].…”
Section: Wwwpsychologyandeducationnetsupporting
confidence: 80%
See 2 more Smart Citations
“…A higher percentage of irregular margin is also observed in another study [22]. This finding is also supported by the study at Dong-A University Hospital and the University of North Carolina at Chapel Hill, USA [22]. Age has no impact margin, a finding similar to a study conducted in Japan [21].…”
Section: Wwwpsychologyandeducationnetsupporting
confidence: 80%
“…Our study has shown that the majority of tumours presented by the patients who have records are irregular margin and hypoechoic regardless of age. A higher percentage of irregular margin is also observed in another study [22]. This finding is also supported by the study at Dong-A University Hospital and the University of North Carolina at Chapel Hill, USA [22].…”
Section: Wwwpsychologyandeducationnetsupporting
confidence: 77%
See 1 more Smart Citation